THE EFFECT OF THE AMMONIUM CONCENTRATION IN THE GROUNDWATER - Kamal, Mohd Zul; Md. Hashim, D; Zin, Mohd Saupi (PEOPLE: International Journal of Social Sciences, 2015)
Groundwater has long been one of the major water resources for a variety of domestic, agricultural, and industrial uses, particular for the regions with limited surface water resources (Zektser, I.S., & Everett, L.G., 2000). This paper discuss to what extent the Ammonium concentration differences by making a comparison with the National Drinking Water Quality 1983 that states the permitted content of Ammonium is at 0.5 mg/l. The Ammonium content in Bachok district is quite a concern as from the data taken in 1990. 1999. and 2011, there’s only one observation well met the standard which is KB 51. KB 34 can be categorized as the most polluted, in 1990, the Ammonium concentration that has been recorded is at 11.2 mg/l. Anthropogenic activities such as urbanization is one of the major component that are causing the high NH4content in the ground water.